Harnessing immunomodulation during DNA damage in Ewing sarcoma - Daley, Jessica D.; Olson, Adam C.; Bailey, Kelly M. (Frontiers in Oncology, 2022)
Ewing sarcoma is a fusion-oncoprotein-driven primary bone tumor most commonly diagnosed in adolescents. Given the continued poor outcomes for patients with metastatic and relapsed Ewing sarcoma, testing innovative therapeutic approaches is essential. Ewing sarcoma has been categorized as a ‘BRCAness’ tumor with emerging data characterizing a spectrum of DNA damage repair defects within individual Ewing tumors, including the presence of EWS-FLI1 itself, recurrent somatic mutations, and rare germline-based defects. It is critical to understand the cumulative impact of various DNA damage repair defects on an individual Ewing tumor’s response to therapy. Further, in addition to DNA-damage-directed therapies, subsets of Ewing tumors may be more susceptible to DNA-damage/immunotherapy combinations given the significant cross-talk between DNA damage and inflammatory pathways in the tumor microenvironment. Here we review potential approaches utilizing DNA-damaging agents as modulators of the Ewing tumor immune microenvironment, with a focus on radiation and opportunities during disease metastasis and relapse.